The Development and Efficiency of Instructional Package on Object Detection by Cooperative Learning Management Using Jigsaw Technique - ทูลธรรม, กิตติ; ทูลธรรม, จารุวรรณ (RMUTI Journal Humanities and Social Sciences, 2016)
This research aimed to develop and find the efficiency of instructional package, academic achievement and complacency of the image processing applications for object detection by cooperative learning management using jigsaw technique. The jigsaw technique model includs 6 steps: 1) preparation, 2) setting a group of learners, 3) giving the document and assignment, 4) setting an expert group, 5) returning home to present knowledge and 6) testing the research instruments were the learning plan, test models, and rating-scale questionnaires. Samples were 25 students who registered in Image Processing course and passed in Computer Programming course of the Rajamangala University of Technology Isan, Bachelor of Technical Education, Computer Engineering Department. The research results were as follows: The degree of the opinions on the model learning of the image processing applications for object detection by cooperative learning management was high level. The efficiency of the model learning of the image processing applications for object detection by cooperative learning management was higher than the standard criteria of meguigans’s formula (1.34). The learning effectiveness of the instructional model was 77.36% (higher than 70% of the hypothesis). The mean of satisfaction of the sampling group was high level.